Medição individualizada em edifícios residenciais : controle e redução do consumo de água potável - Holanda, Marcos Antonio Arruda Guerra de (2007)
Brazil: a water country. This thought could take the people to forget about water conservation. Although Brazil has big watersheds, it also has regions that present serious water supply crisis. The amazon region, with only 5% of brazilian population, stores 80% of water volume of all national territory, while greater part of the population is concentrated in the big cities, needing, at times, a higher volume of water. The individual measurement in residential buildings is one of the most important ways to prevent water lavishness, also to control and to reduce the water consumption. This work tries to show the individual measurement of water as a fair system of price, which permits the control and the reduction on the water consumption. In the firs part, three buildings that had changed from global measurement system to individual measurement system were studied. By these cases, it was possible to show, in the buildings, the distribution of the apartments in classes of consumption, the percentage reduction and the economic feasibility to perform the modification in the measurement system. The second part of this work was to follow a telemetric measurement system in a residential building with individual water meters. The telemetric measurement allowed to know the profile of each consumer, individually, as an important way to plan actions to control and to reduce the water consumption.